IMF Survey, Volume 30, Issue 17. (IMF Survey; IMF Survey, 2001)
Stanley Fischer, IMF First Deputy Managing Director for the past seven years, stepped down from his position at the end of August. Fischer was appointed in 1994 to an initial five-year term and to a second term in 1999. He was previously the Killian Professor and head of the Department of Economics at the Massachusetts Institute of Technology. From 1988 to 1990, he served as Vice President for Development Economics and Chief Economist at the World Bank. Fischer recently spoke with the IMF Survey about his experience at the IMF and the changes he has witnessed during his tenure.